A CLOSE VIEW ON HISTOLOGICAL CHANGES IN ROOTS OF GUAVA VAR. SEEDLESS IN HYDERABAD, SINDH, PAKISTAN - A. Khan; K. A. Khanzada; M. A. Rajput; M. A. Samad; N. Khatoon; S. Waheed (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences)
Guava var. seedless naturally infected with root-knot nematode were fixed, sectioned and examined in detail. Meloidogyne incognita infective second stage juveniles penetrated and moved intercellularly modifying the vascular system and phloem into giant cells of various sizes. After getting mature the females start producing eggs which completely occupy the cortex while in some cells female sections were observed. Necrosis was present with hypertrophy and hyperplasia in cortex cells. Our results suggest selection of resistant guava varieties shall reduce the ability of Meloidogyne incognita damage. In Pakistan, most farmers are small land holders and improved varieties having multiple diseases resistance will be more useful for sustained agricultural production.